PROMISING REGIONAL MODELS IN THE CONTEXT OF MARKETING STRATEGIES FOR TOURISM DEVELOPMENT (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Developing a marketing strategy in the tourism business is a special kind of challenge, especially in the context of digitalization, the implementation of artificial intelligence and the accelerated use of social networks. A key and strategic approach to tourism development and a successful marketing strategy is the use of promising regional models. Tourism managers can very successfully use these models to build effective competitive advantages in the tourism business. The emergence of the need to implement successful marketing strategies in tourism is caused by the constantly increasing level of service in the tourism sector, which is caused by changes in both the environment and changes in the behavior of tourists in their role as consumers. On the other hand, forms of communication are changing, newer means of transport are appearing, natural landscapes and ecosystems are changing, which also remodel tourist behavior. This is precisely where the prerequisites and challenges lie to formulate and describe promising regional models in the context of marketing strategies for tourism development.